RAPD marker use for improving resistance to Helicoverpa zea in corn - da Silva, S. C.; Lemos, MVF; Osuna, JTA (Maydica-ist Sper Cerealicoltur, 2000)
Helicoverpa zea is responsible for great losses to the corn, Zen mays L., crops final productivity, and the best way to control it is by improving genetic resistance. In collaboration with corn improvement and increasing resistance to insects through molecular marker assisted selection, this work had as an objective the selection of resistant (RP) and susceptible progenies (SP) to H. zea based on the RAPD technique. Molecular markers were Found, among the resistant progenies and it is suggested that linkage of these within the Zapalote Chico corn race, be used to extract resistance genes from this race as a donor. The progenies were selected from a population of half-sibs exhibiting a broader genetic base (FCAVJ-VF14). After DNA extraction, two sample bulks were formed; one made up of the six most resistant plants, the other of the six least resistant plants. Eighty-six primers were tested for PCR reactions with the resistant and susceptible bulks and analyzed on agarose electrophoresis for the detection of RAPD band polymorphism. The results of the banding patterns and similarity values indicated a nucleotide sequence amplified by the primer OPC-2 as a possible molecular marker for the identification of resistant progenies and a homology region between them and the Zapalote Chico corn race.
Keywords: Zea mays; RAPD; marker-assisted selection